PENGENDALIAN MODUL ROTARY HANDLING STATION BEBASIS SEQUENTIAL FUNCTION CHART (SFC) - Deli Budiantoro; Agus Halim; Soeharsono G (Program Studi Teknik Mesin Universitas Tarumanagara, 2014)
Abstract: The system used in this day and age has made progress in its operations. In industry itself many use automated systems that only require a small operator to run a tool because it saves time, and safety is guaranteed. In this time the tool discussed Handling Station Rotary pneumatic system uses motion to move this tool. So that the tool can be moved according to plan also required the